Comparison of Protocol Adherence in Maxillofacial Radiology Centers in Tehran Before and After the COVID-19 Pandemic - Soleimanpoor, Sarvin; Khalighi, Hamidreza; Moshfeghi, Mahkameh; Momeni, Amirali (Journal of Dental School, 2025)
Objective(s): The COVID-19 pandemic, caused by SARS-CoV-2, significantly impacted healthcare practices worldwide. Maxillofacial imaging centers were particularly affected due to their close interaction with patients and the use of aerosol-generating procedures. This study aimed to evaluate the changes in personal protective equipment (PPE) use, infection control protocols, and imaging practices before and after the pandemic in maxillofacial imaging centers in Tehran. Methods: This cross-sectional study used a before-and-after design to examine infection control and PPE protocol changes in maxillofacial imaging centers. A questionnaire that covered general information, patient triage, staff performance, and health protocols was distributed to 25 imaging centers and completed by the staff. Data was analyzed utilizing McNemar’s test to compare the conditions before and after the pandemic. Results: The study found a significant increase in the use of PPE among staff and patients following the COVID-19 outbreak. There was a 60% increase in mask usage by staff (P<0.05), and 72% of centers required patients to wear masks after the pandemic (P<0.05). Changes in ventilation systems and social distancing measures were also noted, with 27% of centers installing new ventilation systems after the pandemic (P<0.05). However, the sterilization of imaging equipment remained largely unchanged, with 98% of centers maintaining chemical disinfection practices.